(untitled) (LEARNing Landscapes, 2008)
Collage from "found" visual imagery is widely employed as an accessible medium for expression and illustration in educational, therapeutic, and recreational contexts. Given the history of collage as a strategy of criticism and subversion in the fine arts, visual researchers seek to develop a methodology of collage as a means to knowledge, affording insight into the negotiation and embodiment of media imagery in subjective experience. Highly relevant issues of body image and eating disorders are addressed through the presentation and analysis of a self-study series of collages and life writings. The resulting intuitive "figures" of anorexia demonstrate the creative potential of collage to reconfigure experience excluded from standard texts, and suggest alternative interpretations of both suffering and healing on an individual and cultural level.